INFLUENCED FACTORS TOWARDS THE LANGUAGE SHIFT PHENOMENON OF WOTUNESE - Masrudin Masrudin (Universitas Muhammadiyah Surakarta, 2013)
This study aims to nd out the factors in uence on the language shift of Wotunese. This study was carried out in two villages namely Lampenai Village and Bawalipu Village, Wotu District, East Luwu Regency. The method used was eld survey by distributing questionnaire, interviewing and direct observation for 400 Wotunese, interview the informant sample comprised 400 males and females of Wotunese who live in Wotu area at least 10 years. Their ages are around 10 up to 50 years old. The results show that the determinant factors in uence signi cantly on language shift of Wotunese are age, mobilization, bilingualism and language attitude. Then, the government and the wotunese should do some real actions to save Wotu language from the death language phenomenon. Key words: Language shift, Wotunese, Determinant Factors ABSTRAK Tujuan penelitian ini adalah untuk mengetahui faktor-faktor yang mempengaruhi pergeseran bahasa Wotu. Penelitian ini dilaksanakan di dua desa yakni Desa Lampenai dan Desa Bawalipu Kecamatan Wotu Kabupaten Luwu Timur. Metode yang digunakan adalah metode survei lapangan dengan membagikan angket, wawancara, dan pengamatan langsung terhadap 400 warga masyarakat Wotu. Ke- 400 informan tersebut terdiri dari pria dan wanita yang telah tinggal minimal 10 tahun di daerah Wotu. Hasil penelitian menunjukkan bahwa pergeseran bahasa Wotu sangat dipengaruhi oleh usia, tingkat mobilisasi, kedwibahasaan, dan sikap bahasa. Selanjutnya, pemerintah dan masyarakat Wotu haruslah melakukan tindakan nyata untuk menghindarkan bahasa Wotu dari peristiwa kematian bahasa. Kata kunci: Pergeseran Bahasa, Masyarakat Wotu, Faktor Penyebab